Genome-Wide Analysis of the ATGs Family in Watermelon and the Involvement of ATG8s in Graft Union Formation - Fei Ding; Siqi Cheng; Shaoshuai Fan; Xiulan Fan; Xiaonuan Chen; Jianan Zhang; Yixin Zhang; Yansu Li; Li Miao (Horticulturae)
Autophagy, an evolutionarily conserved process for cellular component degradation and recycling, occurs in yeasts, animals, and plants under both stress and normal conditions. However, the functions of autophagy-related genes (ATGs) in watermelon (Citrullus lanatus) remain uncharacterized. In this study, a phylogenetic analysis identified 27 ATGs belonging to 16 subfamilies in the watermelon genome. A promoter analysis revealed that all the ClaATGs contain multiple photo-responsive elements. Tissue-specific expression profiling showed diverse expression patterns of ClaATGs across different tissues, except for the constitutively expressed ClaATG6. Exogenous independent treatments with glucose, naphthalene acetic acid, and 6-benzylaminopurine induced the expression of most ClaATGs, particularly members of the ClaATG8 subfamily, in the graft unions of normal and etiolated seedlings. A sugar application significantly increased autophagosome numbers during the early stages of graft interface healing, accompanied by the upregulation of ClaATG6, ClaATG8b, ClaATG8i, and ClaTOR, as well as the downregulation of ClaSnRK1. These findings elucidate the roles of ATGs in watermelon graft union formation and provide novel insights into the complex functions of autophagy in plant development and stress responses.